Let the Music Bands Rock! Live Entertainment at Midlands State University Main Campus - Maguraushe, Wonder (Routledge, 2021)
The potential of music to positively influence humans’ well-being has punctuated people’s lives from birth to death. This article explores the state of live music entertainment at Midlands State University main campus in Senga, Gweru. I set out to find out what entertainment opportunities are available for MSU students. Through questionnaires, interviews and focus group discussions, the study solicited students’ and staff members’ views on the leisure activities available on campus. I sought their suggestions on how on-campus entertainment could be improved. The findings show a critical need to reclaim students’ entertainment spaces in Zimbabwe’s tertiary education sector. University management needs to consider facilitating on-campus live music entertainment for students in order to avert the dangers they face when they seek entertainment from places off campus. Students are prone to arbitrary relationships, drug abuse, robbery and exorbitant costs when they visit night clubs in town for entertainment. The university stands to benefit financially if live music shows are managed and organised within its premises. Students’ responses indicate that the MBMT ensembles which currently provide music at formal gatherings need to be augmented with gigs that are purely intended for students’ entertainment. Joint shows with popular music artists recommended by students themselves can be arranged with management, re-aligning their ideology to view live music entertainment in a positive way as a fundraising enterprise. The conclusion proposes the inclusion of a live music entertainment officer in the Student Affairs Department to ensure that students’ entertainment needs are well-planned, managed and availed on-campus.